The Analysis of Law Regarding the Peace against Inheritance Distribution According to Islamic and Civil Laws - Anjani Sipahutar (Budapest International Research and Critics University, 2020)
This study aims to determine the legal strength of a peace institution in the settlement of a judicial case. This is related to the legal arrangement regarding the distribution of inheritance based on Islamic law. The implementation of peaceful institutions in court proceedings can be carried out through the Supreme Court Circular No. 1 of 2002 as follows: so that all panels of judges who hear cases will seriously seek peace by applying the provisions of Article 130 HIR / 154 R.Bg not just a formality for proposing peace, the appointed judge acts as a facilitator who helps the parties in terms of time , the location and collection of data and arguments of the parties in preparation for peace, from the results of this research analysis it can be seen that the distribution of inheritance has practical, systematic and detailed guidelines in the form of Alqurʻan verses, the Prophet's traditions and the law. Islam which has been regulated in Articles 176, 183, Compilation of Islamic Laws shows that the heirs can agree to make peace in the distribution of inheritance.